Minat Mahasiswa Universitas Brawijaya Terhadap Penggunaan Internet Banking Dalam Transaksi Pembayaran SPP: Pendekatan Modified Technology Acceptance Model - Larasati, Cindhe Puspita; Harris, Lutfi (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study examined factors that influence attitude and intention to use internet banking services with Modified Technology Acceptance Model (TAM) approach. The responses in this study are 99 JAFEB UB student which will be and have been using internet banking for university tuition fee payment. The result of this study shows that the perceived usefulness, perceived ease of use, and perceived web security affect the attitude and attitude affect the intention to use internet banking for university tuition fee payment. The result of this research give the reason of the management banking company and internet banking analyst to consider factor of attitude, perceived usefulness, perceived ease of use, and perceived web security in applying and developing internet banking transaction in the banking system. Keyword: Modified Technology Acceptance Model (TAM), internet banking, intention, attitude, perceive web security.